1991
DOI: 10.1021/jf00011a012
|View full text |Cite
|
Sign up to set email alerts
|

Attempt for an on-line size exclusion chromatography-gas chromatography method for analyzing pesticide residues in foods

Abstract: Advantages and limitations of an on-line SEC-GC method for the analysis of pesticide residues in foods are discussed; results are shown for olive oil, fat extracts of chicken and fish, and lettuce. The method allows automated integration of sample preparation into the GC analysis and eliminates corresponding manual work. It is well suited as a multimethod for analyzing many strongly differing components at the same time, and, as high molecular weight materials are removed, it allows on-column introduction into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The triglycerides were more strongly retained than the pesticides in the LC system and so were eluted after them. The problem of the triglyceride peak tailing into the pesticide fraction when NPLC is used (24) does not arise in this case, which is a considerable advantage bearing in mind the large size of the triglyceride peak. Hence, the use of RPLC in the preseparation step is an interesting alternative.…”
Section: Resultsmentioning
confidence: 99%
“…The triglycerides were more strongly retained than the pesticides in the LC system and so were eluted after them. The problem of the triglyceride peak tailing into the pesticide fraction when NPLC is used (24) does not arise in this case, which is a considerable advantage bearing in mind the large size of the triglyceride peak. Hence, the use of RPLC in the preseparation step is an interesting alternative.…”
Section: Resultsmentioning
confidence: 99%
“…Previous works using on-line LC-GC methods for the analysis of pesticide residues in edible oil mainly refer to the use of normal phase in the LC separation step. Grob and Kälin [11] described on-line size exclusion chromatography-gas chromatography (SEC-GC) for the determination of chlorinated pesticides in food containing fat, although the same authors indicated that the amount of triglycerides transferred disturbs the GC system. Coupled SEC-GC methods for organophosphorous pesticide detection in edible oils have also been described [1,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Examples include on-line SPE-GC for water analysis and on-line NPLC-GC for food analysis and petrochemical analysis. , A very attractive application is the on-line coupling of GPC to GC which is typically used to remove fats and pigments (chlorophyll). This was already recognized in the early 1990s. , Coupling of GPC to GC is very challenging because of the very large volume fractions involved. After quite extensive optimization, one robust application was presented (organophosphorus pesticides in olive oil, , ).…”
mentioning
confidence: 99%
“…This was already recognized in the early 1990s. 21,22 Coupling of GPC to GC is very challenging because of the very large volume fractions involved. After quite extensive optimization, one robust application was presented (organophosphorus pesticides in olive oil, 23,24 ).…”
mentioning
confidence: 99%